(untitled) (UBS Scientific Bulletin, 2024)
this article reflects on the rational management of the educational process in secondary schools and the role of the class monk in the education of his students, activities, responsibility for establishing children’s lives, organizing and raising a team, responsibility for educational work in the classroom.